Efficacy of high-power laser therapy combined with exercise on wrist pain, function and joint position sense in female gymnasts with non-specific chronic wrist pain - Dina Othman Shokri Morsi Galal; Hanaa Mohsen Abd-Elfattah; Hend Reda Sakr; Noha Elserty; Mina Atef Georgui Elias (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.